Boundary value problems of conjugate and generalized k-holomorphic functions in ℂ2 - Cui, Yanyan; Wang, Chaojun; Xie, Yonghong; Qiao, Yuying (Acta mathematica scientia, 2024)
In this paper, conjugate k -holomorphic functions and generalized k -holomorphic functions are defined in the two-dimensional complex space, and the corresponding Riemann boundary value problems and the inverse problems are discussed on generalized bicylinders. By the characteristics of the corresponding functions and boundary properties of the Cauchy type singular integral operators with conjugate k -holomorphic kernels, the general solutions and special solutions of the corresponding boundary value problems are studied in a detailed fashion, and the integral expressions of the solutions are obtained.